1964
DOI: 10.3758/bf03342947
|View full text |Cite|
|
Sign up to set email alerts
|

Modification by early experience of the tendency toward gregariousness in rats

Abstract: AbstraetAfter they were weaned, albino rats were housed individually (Group 1), in pairs (Group 2), and in groups of five (Group 3). After 18 weeks of housing under these circumstances, the tendency toward gregariousness, defined as a function of the number of approaches to the other rat of the same species, was tested. Group 3 showed the strongest tendency toward gregariousness, Group 2 a weaker tendency, and Group 1 the weakest. Introduetlon Some research evidence (Denenberg, 1963;McClelland, 1956) has shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…their own species. As in the cohabitation studies, evidence for this generalization is available for various mammalian species, including rats (Angermeier, 1960;Ashida, 1964), cats (Kuo, 1960;Schneirla & Rosenblatt, 1961), sheep (Scott, 1945), and monkeys (Harlow, 1962;Mason, 1960;Sackett, Porter, & Holmes, 1965). These results are generally consistent with the interpretation that the conspecific object may constitute a disruptive cue, or at the least, not be required for the performance of the isolated animal's basic response repertoire.…”
Section: Effects Of Extended Exposurementioning
confidence: 53%
“…their own species. As in the cohabitation studies, evidence for this generalization is available for various mammalian species, including rats (Angermeier, 1960;Ashida, 1964), cats (Kuo, 1960;Schneirla & Rosenblatt, 1961), sheep (Scott, 1945), and monkeys (Harlow, 1962;Mason, 1960;Sackett, Porter, & Holmes, 1965). These results are generally consistent with the interpretation that the conspecific object may constitute a disruptive cue, or at the least, not be required for the performance of the isolated animal's basic response repertoire.…”
Section: Effects Of Extended Exposurementioning
confidence: 53%
“…Furthermore, there are discrepancies concerning the effects of grouping vs. isolation on measures of sociability. In some situations, isolated rats seemed less gregarious (Angermeier, 1959;Ashida, 1964), and in others, more so (Casey, 1962;Latane, Cappell, & Joy, 1970;Shelley & Hoyenga, 1966, 1967. In one situation, gregariousness was species dependent, with grouped Peromyscus spending more time than isolated Peromyscus near a conspccific, and the reverse being true for C57 mice (Bronson, 1963).…”
mentioning
confidence: 99%
“…Investigators report individual and group housing have no effect on gregarious behavior (Bayroff, 1936), individual housing increases gregarious behavior (Latane, Cappel, & Joy, 1970;Latane, Schneider, Waring, & Zweigenhaft, 1971;Salazar, 1968;Shelley & Hoyenga, 1966;Sloan & Latane, 1974), and -group housing increases gregarious behavior (Ashida, 1964;Stevenson & SimmeL 1967). Latane et al (I970) have suggested gregariousness has drive-like characteristics and is responsive to deprivation.…”
mentioning
confidence: 99%